Pelatihan Penulisan Artikel Ilmiah yang Layak Terbit Bagi Guru - Fitraini, Depi; Nurdin, Erdawati; Nufus, Hayatun; Hasanuddin, Hasanuddin (LSM Catimore dan Sahabat, 2024)
This dedication is carried out against the backdrop of teachers' limited knowledge about scientific writing. However, scientific works play a strategic role in the efforts to develop the teaching profession. Therefore, this dedication is essential with the aim of providing understanding and training the skills of the Mathematics Subject Teacher Professional Development (MGMP Matematika) in Junior High Schools in Pekanbaru City about the principles and methods of creating scientifically sound articles and the venues for publishing scientific articles based on the results of classroom cction research (PTK)